2011
DOI: 10.1007/s10461-011-9924-z
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Change in Cognitive Function and Medication Adherence in HIV-Infected Adults

Abstract: Neuropsychological (NP) dysfunction has been linked to poor medication adherence among HIV-infected adults. However, there is a dearth of research examining longitudinal changes in the relationship between NP status and adherence rates. We hypothesized that declines in NP functioning would be associated with a corresponding decline in medication adherence while stable NP functioning would be associated with stable or improving adherence rates. Participants included 215 HIV-infected adults who underwent cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 24 publications
(20 reference statements)
3
76
1
1
Order By: Relevance
“…Neurocognitive deficits after transplantation are important because intact neurocognitive functioning is critical for decision-making capacity and for the ability to manage a complex medical regimen, both of which are essential elements of post-transplant care (28). Moreover, studies of other medical patients have suggested that neurocognitive deficits in executive function, memory, and working memory are associated with poorer medication adherence (5,(29)(30)(31), including patients with HIV (31-33) and cardiovascular disease (5) and healthy older adults (29). Indeed, lower neurocognitive function has been associated with nearly four times greater risk of medication noncompliance in older adults (29).…”
Section: Discussionmentioning
confidence: 99%
“…Neurocognitive deficits after transplantation are important because intact neurocognitive functioning is critical for decision-making capacity and for the ability to manage a complex medical regimen, both of which are essential elements of post-transplant care (28). Moreover, studies of other medical patients have suggested that neurocognitive deficits in executive function, memory, and working memory are associated with poorer medication adherence (5,(29)(30)(31), including patients with HIV (31-33) and cardiovascular disease (5) and healthy older adults (29). Indeed, lower neurocognitive function has been associated with nearly four times greater risk of medication noncompliance in older adults (29).…”
Section: Discussionmentioning
confidence: 99%
“…52,53 An earlier US cohort study, enrolled between 2001 and 2005, found declining cognitive function in 35% of the 215 patients followed up (of 276 originally enrolled), but there was a 56% prevalence of "substance abuse or dependence", and treatment and adherence may have been suboptimal by current standards. 54 Other classic screening criteria are that the natural history of a condition, including its development from silent to clinical disease, should be well-understood, and there should be a recognizable latent or early symptomatic stage. Beyond the beneficial effects of ART, physicians are faced with uncertainty about how patients' cognitive difficulties will evolve over time, and more longitudinal studies are needed.…”
Section: Outcomes and Impacts Of Hiv-associated Nci In Treated Patientsmentioning
confidence: 99%
“…Not surprisingly, MA abuse increases the risk for neurocognitive impairment among HIV-infected persons (Carey et al, 2006;Rippeth et al, 2004), especially with HIV/Hepatitis C Virus (HCV) coinfection (Cherner et al, 2005;Letendre et al, 2007). Greater cognitive dysfunction is associated with poor HIV clinical outcomes including medication nonadherence (Becker, Thames, Woo, Castellon, & Hinkin, 2011) and worsened quality of life (Parsons, Braaten, Hall, & Robertson, 2006). Therefore, medications that reduce neuroinflammation in HIV-infected substance users may improve HIV and substance-related clinical outcomes via improvements in neurocognitive functioning.…”
Section: Neuroinflammation and Hivmentioning
confidence: 99%